KOGNISI SOSIAL PADA NOVEL SUTI KARYA SAPARDI DJOKO DAMONO ANALISIS WACANA MODEL VAN DIJK - Azmi Azhara; Dheni Harmaen; Aries Setia Nugraha (STKIP Subang, 2023)
This study aims to analyze social cognition in the novel Suti by Sapardi Djoko Damono, discourse analysis of the van Dijk model, and utilize the results of this analysis as an alternative teaching material for class XII high school students. This research is a descriptive qualitative research, in which the data analysis results will be described in a narrative manner. The data source in this analysis is the novel Suti by Sapardi Djoko Damono. Novel Suti by Sapardi Djoko Damono and several books or other reading materials that can support research. Suti's novel consists of 58 data on social cognition, 27 data for social cognition knowledge and 31 data for social cognition opinions and attitudes. The findings from the results of the analysis of this novel show that van Dijk's type of social cognition used is social cognition of knowledge and attitude opinion, because this novel shows some of the author's knowledge from personal experience, traditions and culture that they adhere to. Furthermore, regarding opinion, attitudes are described by the author expressing his opinion and attitude regarding a problem in the novel. Suti has various views, opinions, and attitudes towards issues in the story.